Peningkatan Hasil Belajar PJOK melalui Metode Demonstrasi pada Siswa Kelas IX-B SMP Negeri 2 Sikur Kecamatan Sikur - Rahmat, Lalu (MASALIQ, 2022)
Through the use of the Demonstration method is a concept of learning activities that assist teachers in carrying out practical Physical Education learning activities by trying to maximize the role of students, especially how students are able to carry out practical movements as explained and exemplified by the teacher. With this concept, learning outcomes are expected to be more meaningful for students. The practical learning process takes place in the form of student practice activities on the material being discussed at that time. The quality of practical learning is more important than the results. The purpose of this class action research (CAR) is to want to know. results of increasing PJOK learning through the use of demonstration learning methods in class IX-B students of SMPN 2 Sikur, Sikur District, 2020/2021 academic year. In this classroom action research (CAR) it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase students' learning completeness in a classical manner, namely in cycle I by 70%, it could increase to 90% in cycle II. The results of this classroom action research show that learning by applying the demonstration method can improve PJOK learning outcomes.